Late-onset pulmonary arterial hypertension after successful early arterial switch surgery for simple transposition of the great arteries - Smedema, Jan-Peter; Pistorius, Lou; Brink, Johan (SA Heart Journal, 2017)
Pulmonary arterial hypertension rarely develops in patients with simple transposition of the great arteries who undergo neonatal surgical correction. We describe a young male patient who was diagnosed with severe pulmonary arterial hypertension 14 years after neonatal arterial switch surgery. The relevant literature is briefly reviewed. Clinicians should be aware of this rare, late, and potentially life-threatening condition. Continued long-term follow up of these patients should be provided. Early diagnosis and treatment with combination therapy may improve outcomes